Successful aortic valve replacement for aortic regurgitation associated with osteogenesis imperfecta. - Weisinger, B (1975)
The occurrence of severe aortic regurgitation in two patients with typical findings of osteogenesis imperfecta is described. Both patients manifested severe haemodynamic abnormalities and underwent successful aortic valve replacement. The operative and pathological findings are discussed.